Аеродинамічна сторона проблеми зниження вібронапруженості лопаток осьового компресора газотурбінного двигуна - Красников, Олександр Олегович; Кухтін, Юрiй Петрович (Національний технічний університет "Харківський політехнічний інститут", 2022)
Розглянута аеродинамічна сторона проблеми підвищення вібронадійності лопаток осьового компресора. Чисельним шляхом визначені аеродинамічні навантаження, що діють на лопатки осьового компресора від следового й потенційного впливу сусідніх вінців. За результатами розрахунків проведений аналіз інтегральних і розподілених аеродинамічних навантажень на робочу лопатку в порівнюваних варіантах ступенів. Для отриманих розподілених навантажень полічені згібні напруги по стрижневій теорії.

Consideration was given to the design methods available in practice for an increase in the vibration reliability of the blades of axial compressor. The problem was formulated to show the possibility of the reduction of the strain in the blade nib by the control of the exciting aerodynamic forces. When it is impossible to eliminate the resonance completely and the measures taken to increase structural damping fail to give positive effect it is reasonable to make use of the possibility of the strain reduction by the control of the excitation source. Consideration was given to the aerodynamic aspect of the problem relating to an increase of the vibration reliability of the blades of axial compressor. The aerodynamic loads affecting the axial compressor blades ranging from the trace to potential effects of adjacent shrouds were determined numerically. The program package SUnFlow with the realized in it numerical integration of the Reynolds-averaged Naiver-Stocks equations was used as an investigation tool. The high-pressure compressor stage containing 120 blades of the input guide unit, 83 operating blades and 104 blades of the guide system was used as a test object. The computations were done for the initial structure of the compressor stage and for the stage structure with embedded measures in the form of the variable- pitch input guide unit.he blade nib by the control of the exciting aerodynamic forces.
Aerodynamic aspect of the problem relating to the reduction of the vibration strain in the axial compressor blades of the gas turbine engine
Keywords: резонанс; вібронадійність; збудливі сили; робочі лопатки компресора; різнокроковий напрамний апарат; resonance; vibration reliability; exciting forces; operating compressor blades and variable-pitch guide unit